2011
DOI: 10.1029/2011jc006955
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal upwelling resonantly driven by sea breezes around an Adriatic island

Abstract: Diurnal coastal upwelling was previously observed when sea breezes were exceptionally strong, or when the process occurred close to critical latitudes (30°N, 30°S) where local inertial oscillations may be resonantly excited. Our data collected in the Adriatic show that the pronounced diurnal upwelling is also possible under milder wind‐forcing and outside critical latitudes. It is found that the thermocline recorded in the summer of 2006 at the south coast of the island of Lastovo was subject to diurnal variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…For example, several studies have found that diurnal wind forcing is a major mechanism driving significant temperature oscillations, some of which are on the order of seasonal fluctuations [ Kaplan et al ., ; Woodson et al ., ; Bonicelli et al ., ; Aristizábal et al ., ]. Local winds have also been shown to influence a host of physical processes including local diurnal upwelling [ Woodson et al ., ], inertial current oscillations [ Orlić et al ., ; Lucas et al ., ], internal wave development [ Lerczak et al ., ], local heat budgets [ Suanda et al ., ], modulation of buoyant plume fronts and the subsequent evolution of nonlinear internal waves [ Woodson et al ., ; Walter et al ., ], and local circulation patterns [ Rosenfeld , ; Woodson et al ., ; Bonicelli et al ., ]. From a biological perspective, local diurnal winds have been shown to play a fundamental role in phytoplankton dynamics [ Lucas et al ., ] and spatial patterns of barnacle settlement [ Bonicelli et al ., ], thereby affecting ecosystem productivity and the transport of larvae.…”
Section: Introductionmentioning
confidence: 99%
“…For example, several studies have found that diurnal wind forcing is a major mechanism driving significant temperature oscillations, some of which are on the order of seasonal fluctuations [ Kaplan et al ., ; Woodson et al ., ; Bonicelli et al ., ; Aristizábal et al ., ]. Local winds have also been shown to influence a host of physical processes including local diurnal upwelling [ Woodson et al ., ], inertial current oscillations [ Orlić et al ., ; Lucas et al ., ], internal wave development [ Lerczak et al ., ], local heat budgets [ Suanda et al ., ], modulation of buoyant plume fronts and the subsequent evolution of nonlinear internal waves [ Woodson et al ., ; Walter et al ., ], and local circulation patterns [ Rosenfeld , ; Woodson et al ., ; Bonicelli et al ., ]. From a biological perspective, local diurnal winds have been shown to play a fundamental role in phytoplankton dynamics [ Lucas et al ., ] and spatial patterns of barnacle settlement [ Bonicelli et al ., ], thereby affecting ecosystem productivity and the transport of larvae.…”
Section: Introductionmentioning
confidence: 99%
“…This consideration led us to exclude the possibility of the low-frequency limit extension of the internal spectrum. Orlić et al (2011) and Mihanović et al (2009) found that summertime stratification occasionally generates internal coastal waves that travel daily around an island in the southern Adriatic Sea, creating the conditions for resonant excitation of the diurnal frequency by sea breeze and/or diurnal tides. In particular, Orlić et al (2011) forced the Princeton Ocean Model by real wind stress and found that an intensification of the diurnal signal, similar to that found in our data, is not possible without the topographic effect.…”
Section: Possible Generation Mechanismsmentioning
confidence: 99%
“…Orlić et al (2011) and Mihanović et al (2009) found that summertime stratification occasionally generates internal coastal waves that travel daily around an island in the southern Adriatic Sea, creating the conditions for resonant excitation of the diurnal frequency by sea breeze and/or diurnal tides. In particular, Orlić et al (2011) forced the Princeton Ocean Model by real wind stress and found that an intensification of the diurnal signal, similar to that found in our data, is not possible without the topographic effect. In the Otranto area the topography is characterized by a gently increasing slope from the coast to the position of the station St2; seaward from that location the bottom slope abruptly increases, reaching its maximum value between St2 and St3 (Fig.…”
Section: Possible Generation Mechanismsmentioning
confidence: 99%
“…[] the diurnal breezes in the Adriatic Sea may have a very strong impact on diurnal variations in the flow field superimposed on tidal oscillations, and thus affect these latter. A possible explanation to the fact that the diurnal constituents are affected by relatively larger errors might then be related to the inability of the model to capture wind‐related processes mainly on diurnal frequencies—such as the summer sea breeze cycle [ Orlić et al ., ], which may interact with the tidal amplitude oscillations and phases. The best result in amplitude is achieved for the reproduction of the most energetic frequency, M2, with an average error around the basin of only 2%.…”
Section: Validation Of the Baroclinic Ocean Model With Tidal Componentsmentioning
confidence: 99%